SIMULATION OF STEEL OXIDATION USING Mn, Si, Al IN THE COMPUTING ENVIRONMENT OF MathCAD USING DIFFERENT METHODS OF VISUALIZING CALCULATION RESULTS - Bytkin, Serhii; Kriytska, Tetyana (Scientific Journal "Metallurgy", 2023)
For modeling the deoxidation of traditional impurities (Mn, Si, Al), a method of using MathCAD is proposed, which includes various elements of calculation and visualization of the obtained results. It is shown by the method of a computational experiment that when the deoxidizer, R, is introduced, that is, an increase in [R], there is a nonlinear decrease in the concentration of dissolved oxygen [O] and the modulus of the numerical value (d[O])/dR. Analysis of the nature of the change in the deoxidation reaction rate, d/dR(d[O])/dR, indicates the existence of a concentration R at which a “break” in the dependence is observed (a decrease in the slope of the function d/(dR)(d[O])/ dR=f([R]), that is a pronounced decrease in the rate of change in the concentration [O]. In other words, starting from a certain value of [R], increasing the deoxidizer concentration is not effective. Optimal calculated concentrations of deoxidizers are proposed. The marginally necessary concentrations of deoxidizers [mass %], at which the rate of reduction of the content of [O] dissolved in steel is practically zero, are: [Mn] ≈ 0.85; [Si] ≈3.35; [Al]≈0.05. The technological concentration of [Al] can probably be reduced to 0.015% (the “break-even” point), which theoretically allows [O] to be reduced to 1.7·10-3 ppm at t 1600 °C. It is reasonable to assume that for deoxidation for steel using silicon, the optimal concentration is [Si] 0.5%. For manganese, this approach is not acceptable, for a weak deoxidizer, it is impractical to use the second “break” point, because at a concentration of [Mn] 0.207%, [O] 0.2% is observed in the calculation experiment, and if we apply the numerical value [Mn] 0.85%, then the calculated value [O] 0.05%, that is, four times less. The proposed modeling technique makes it possible to determine the maximum allowable concentration of dissolved in metal silicon [Si] used for its deoxidation, which corresponds to its concentration, at which a change in the direction of the binding reaction [O] is observed according to the principle of Le Chatelier – Brown. At [Si] 3.35 mass %, the rate of deoxidation is practically zero. A change (increase) in the concentration of [Si] leads to a disturbance of the equilibrium in the direction opposing the change made, namely: an increase in the concentration of the deoxidizer leads to an increase in the rate of increase in the concentration of oxygen.